Depressive Symptoms, Anxiety Disorder, and Suicide Risk During the COVID-19 Pandemic - Pera, Aurel (Frontiers in Psychology, 2020)
This study reviews the existing literature on psychiatric interventions for individuals affected by the COVID-19 epidemic. My article cumulates previous research on how extreme stressors associated with COVID-19 may aggravate or cause psychiatric problems. The unpredictability of the COVID-19 epidemic progression may result in significant psychological pressure on vulnerable populations. Persons with psychiatric illnesses may experience worsening symptoms or may develop an altered mental state related to an increased suicide risk. The inspected findings prove that psychological intervention measures for patients affected by the epidemic should be designed and personalized adequately. Preventive measures seek to decrease infection rates and cut down the risk of the public healthcare system to eventually be overburdened. Throughout the COVID-19 crisis, people with psychiatric illnesses may confront a decrease in mental health services. As limitations in the current review, by focusing only on articles published in journals indexed in Web of Science, Scopus, and ProQuest, I inevitably disregarded other valuable sources. Subsequent research directions should clarify the effectiveness of online mental health services in providing remote psychiatric interventions to individuals affected by the COVID-19 epidemic.